(untitled) (Journal of the College of Basic Education, 2025)
As a result of the growing need witnessed in recent years, which has paved the way for adopting modern inputs to education with the aim of satisfying the needs that remove all difficulties towards the process of professional preparation of the specialist (teacher) in the field of art education and framing it according to the trends of sustainable development, and accordingly, the researcher set out to establish solutions to the problem addressed by the study of the professional roles of the teacher in light of the indicators reflected by the current research in the field of sustainable development, and after verifying the professional level of art education teachers in the primary stages, the current research required the necessity of investigating the literary brush specific to this field, as the researcher presented and discussed a group of topics concerned with the developmental and professional field of art education teachers, and mobilizing the mechanisms of their interaction with the trends of sustainable development and in a way that reflects the characteristics of the teacher in this field during its application in educational situations, so the current research community included art education teachers in primary schools affiliated with the General Education Directorates - (Governorate -: - Baghdad) in the academic year 2024-2025, and a sample of (30) male and female art education teachers was selected for the research. An observation form was also designed based on the dimensions of sustainable development, reinforced by a selection of educational indicators as one of the current research tools. The researcher then verified its validity, which reached (85%), and its stability with an agreement coefficient of (88.39). The application process of the research tool was also conducted in order to identify the sequential effect of the indicators of sustainable development in its ability to create and activate the professional role of the teacher. Thus, the stage of obtaining the results of the study was reached, represented by the possibility of activating the trend of sustainable development within educational situations, in addition to revealing some aspects of strength and failure within these situations with their social, environmental and economic aspects practiced by art education teachers. Therefore, the researcher recommended taking some treatments and approaches that can achieve the professional role of sustainable development for the art education teacher within educational situations.